Morphostatic Speciation within the Dagger Nematode Xiphinema hispanum-Complex Species (Nematoda: Longidoridae) - Antonio Archidona-Yuste; Ruihang Cai; Carolina Cantalapiedra-Navarrete; José A. Carreira; Ana Rey; Benjamín Viñegla; Gracia Liébanas; Juan E. Palomares-Rius; Pablo Castillo (Plants, 2020)
Dagger nematodes of the genus Xiphinema include a remarkable group of invertebrates of the phylum Nematoda comprising ectoparasitic animals of many wild and cultivated plants. Damage is caused by direct feeding on root cells and by vectoring nepoviruses that cause diseases on several crops. Precise identification of Xiphinema species is critical for launching appropriate control measures. We deciphered the cryptic diversity of the Xiphinema hispanum-species complex applying integrative taxonomical approaches that allowed us to verify a paradigmatic example of the morphostatic speciation and the description of a new species, Xiphinema malaka sp. nov. Detailed morphological, morphometrical, multivariate and genetic studies were carried out, and mitochondrial and nuclear haploweb analyses were used for species delimitation of this group. The new species belongs to morphospecies Group 5 from the Xiphinema nonamericanum-group species. D2-D3, ITS1, partial 18S, and partial coxI regions were used for inferring the phylogenetic relationships of X. malaka sp. nov. with other species within the genus Xiphinema. Molecular analyses showed a clear species differentiation not paralleled in morphology and morphometry, reflecting a clear morphostatic speciation. These results support the hypothesis that the biodiversity of dagger nematodes in southern Europe is greater than previously assumed.